Digital Environmental Conservation Literacy for Youth in Bojongsari Village, Indramayu Regency - Mira Novita Rahman; Asep Bayu Dani Nandiyanto (Open Global Scientific Journal, 2022)
This study aims to provide literacy and also build awareness of youth in the Bojongsari village, Indramayu Regency regarding how to maintain and preserve the surrounding environment through digital media. The material was delivered online (in the network) through WhatsApp groups to 20 young men and women aged 14 to 25 years. The learning media used are short videos, educational posters and powerpoints, with pretest and posttest as a benchmark for understanding the material presented. During the lecture, the researchers also implemented a movement to reduce plastic waste for 7 consecutive days called the #TumblerChallenge and #ByeByePlastik movements. The results of this study indicate that there is an increase between the pretest and posttest scores. This can be proven from the 20 pretest and posttest questions given, there is an increase in the average score from 80.75 to 88.13. With literacy through digital media with interesting content on how to protect and preserve the environment, it can provide knowledge and raise awareness to always protect and preserve the environment.